Synthesis of carbon nanotube fibers using the direct spinning process based on Design of Experiment (DOE). (April 2016) - Lee, Sung-Hyun; Park, Junbeom; Kim, Hye-Rim; Lee, Taeseon; Lee, Jaegeun; Im, Yong-O.; Lee, Cheol-Hun; Cho, Hyunjung; Lee, Hyeseon; Jun, Chi-Hyuck; Ahn, Yu-Chan; Lee, In-Beum; et al.
Abstract: The optimum synthesis conditions for carbon nanotube (CNT) fibers were investigated using the Design of Experiment (DOE) technique. Direct spinning processes are governed by a variety of experimental factors: the methane flow rate, ferrocene flow rate, sulfur flow rate, hydrogen flow rate, water flow rate, and reaction temperature. The process was optimized in two stages that addressed first the Fractional Factorial Design (FFD) and then the Response Surface Methodology (RSM). Results from each experiment were classified according to a 6-step rating system: nothing(1), black gas(2), dust(3), ribbon or film(4), fiber(5), or continuous fiber(6). In the first step, three major factors (methane, sulfur, temperature) were identified as important among the six experimental factors tested using FFD. The effects of the major factors and the interactions were analyzed through the main effect plot and the interaction plot. In the second step, the experimental conditions were optimized using a model equation derived from Box-Behnken design experiments. Finally, the CNT fibers were continuously synthesized under the optimum conditions. The synthesized CNT fibers mainly consisted of single-walled CNTs (SWCNTs) 1.2–3.8 nm in diameter. The IG /ID ratio of the CNT fibers was 48. This work provides a useful methodology for synthesizing the CNT fibers.